Effect of Pulsatile Flow Waveform and Womersley Number on the Flow in Stenosed Arterial Geometry. (25th November 2012) - Banerjee, Moloy Kumar; Ganguly, Ranjan; Datta, Amitava
Abstract : The salient hemodynamic flow features in a stenosed artery depend not only on the degree of stenosis, but also on its location in the circulatory system and the physiological condition of the body. The nature of pulsatile flow waveform and local Womersley number vary in different regions of the arterial system and at different physiological state, which affects the local hemodynamic wall parameters, for example, the wall shear stress (WSS) and oscillatory shear index (OSI). Herein, we have numerically investigated the effects of different waveforms and Womersley numbers on the flow pattern and hemodynamic parameters in an axisymmetric stenosed arterial geometry with 50% diametral occlusion. Temporal evolution of the streamlines and hemodynamic parameters are investigated, and the time-averaged hemodynamic wall parameters are compared. Presence of the stenosis is found to increase the OSI of the flow even at the far-downstream side of the artery. At larger Womersley numbers, the instantaneous flow field in the stenosed region is found to have a stronger influence on the flow profiles of the previous time levels. The study delineates how an approximation in the assumption of inlet pulsatility profile may lead to significantly different prediction of hemodynamic wall parameters.